Fibrotic Tissue and Middle Turbinate Exhibit Similar Mechanical Properties. Is Fibrosis a Solution in Nasal Polyposis? - Gregório,Luciano (2017)
Abstract Introduction Nasal polyposis (NP) is a chronic inflammatory condition of the upper airway characterized by overgrowth of nasal mucosa. Recent studies have shown a mechanical dysfunction in the nasal polyp tissue. Objective This study aims to evaluate the mechanical properties of nasal fibrotic tissue. Method This study was an institutional review board approved translational study in 20 participants (8 patients with NP, 7 patients with nasal synechiae, and 5 subjects without sinus disease (control group). We used Controlled Disc Stimulation equipment to compare the curve Pressure/Volume created during the saline solution infusion. Results The increase of pressure in response to solution injection was lower in the nasal polyp group when compared with control middle turbinate group and fibrotic group. No significant difference was found in the pressure response during solution injection between fibrotic group and control middle turbinate group. Inferior turbinate group showed significant difference when compared with control middle turbinate group. Conclusion Themechanical dysfunction found in the nasal mucosa of patients with NP provides new insight into this condition. These data allow the belief that the fibrosis has a potential role in increasing interstitial hydrostatic pressure and, consequently, mitigating edema formation in NP.